2015
DOI: 10.1007/s12541-015-0243-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of light weight concrete at elevated temperature

Abstract: This study provides an experimental investigation on the mechanical properties of concrete with thermal expansion at elevated temperatures. To understand the mechanical properties at elevated temperature, normal and light weight concrete of 60 MPa grade was exposed to temperature range 20 (room temperature) to 700ºC under 0.0 f cu (compressive strength of concrete at room temperature, f cu ), 0.2 f cu , 0.4 f cu load conditions and compressive strength, elastic modulus, thermal strain and creep at target tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…This higher reduction is because of the inbuilt vapor pressure after subjected to high temperature. These results are in accordance with Kim et al (2015). It was reported that the strength of normal weight concrete decreased more sharply than the light weight concrete.…”
Section: Introductionsupporting
confidence: 91%
“…This higher reduction is because of the inbuilt vapor pressure after subjected to high temperature. These results are in accordance with Kim et al (2015). It was reported that the strength of normal weight concrete decreased more sharply than the light weight concrete.…”
Section: Introductionsupporting
confidence: 91%
“…Thus, their application in external walls for multiple fire/bushfire exposures is limited. Many research studies have also reported similar strength reduction in other lightweight masonry and concrete at elevated temperatures in comparison with conventional cement-sand mixes (Kim et al, 2015;Hernandez-Olivares and Barluenga, 2004;Aydın, 2008;Demirel and Keles ¸temur, 2010;Mydin and Wang, 2012). Cree et al (2013) stated that conventional concrete loses considerable unrecoverable strength when exposed to temperatures greater than 300 8C because of the variation of its chemical composition and physical structure (Arioz, 2007).…”
Section: Introductionmentioning
confidence: 85%
“…However, in actual concrete structures, the concrete members are stressed by the designed load and constrained by other members. Therefore, concrete in structures exposed to high temperatures is practically always heated under stress [ 15 , 16 ], and the thermal behaviors of stressed concrete are different from those of unstressed concrete [ 16 , 17 ]. The test on stressed concrete during heating has been employed by many researchers.…”
Section: Introductionmentioning
confidence: 99%
“…The same conclusion was reached by Tao et al [ 25 ], when a preload at a pre-stress ratio of 0.2 was applied on self-compacting concrete cylinder specimens. Kim et al did a series of experiments on the stressed concrete [ 7 , 16 , 26 ], and carried out experiments on the compressive strengths of light-weight and normal concrete at high temperature at different pre-stress ratios [ 16 ]. The results showed that the light weight concrete had a higher compressive strength, and Kim suggested that the stress applied to the concrete during heating should be controlled at less than 40% of the concrete strength at room temperature.…”
Section: Introductionmentioning
confidence: 99%